Dynamics of rising CO2 bubble plumes in the QICS field experiment: Part 1 – The experiment. (July 2015) - Sellami, Nazmi; Dewar, Marius; Stahl, Henrik; Chen, Baixin
Highlights: The CO2 bubbles leaked from QICS exp. are detected at diameters from 3 to 12 mm. Velocities of leaked bubbles are at 20–45 cm/s. Breakup and coalescence of bubbles are detected by a high-speed camera. The dynamics of leaked bubbles are analysed in terms of Eötvös and Reynolds numbers. Abstract: The dynamic characteristics of CO2 bubbles in Scottish seawater are investigated through observational data obtained from the QICS project. Images of the leaked CO2 bubble plume rising in the seawater were captured. This observation made it possible to discuss the dynamics of the CO2 bubbles in plumes leaked in seawater from the sediments. Utilising ImageJ, an image processing program, the underwater recorded videos were analysed to measure the size and velocity of the CO2 bubbles individually. It was found that most of the bubbles deform to non-spherical bubbles and the measured equivalent diameters of the CO2 bubbles observed near the sea bed are to be between 2 and 12 mm. The data processed from the videos showed that the velocities of 75% of the leaked CO2 bubbles in the plume are in the interval 25–40 cm/s with Reynolds numbers (Re) 500–3500, which are relatively higher than those of an individual bubble in quiescent water. The drag coefficient C d is compared with numerous laboratory investigations, where agreement was found between the laboratory and the QICS experimental results with variations mainly due to the plume induced vertical velocity component of the seawater current and the interactions between the CO2 bubbles (breakup and coalescence). The breakup of the CO2 bubbles has been characterised and defined by Eötvös number, Eo, and Re .